Cortical and motor responses to acute forced exercise in Parkinson's disease. (March 2016) - Alberts, Jay L.; Phillips, Michael; Lowe, Mark J.; Frankemolle, Anneke; Thota, Anil; Beall, Erik B.; Feldman, Mary; Ahmed, Anwar; Ridgel, Angela L.
Abstract: Introduction: Studies in animal models of Parkinson's disease (PD) have suggested that the rate of exercise performance is important in treatment efficacy and neuroprotection. In humans with PD, lower-extremity forced-exercise (FE) produced global improvements in motor symptoms based on clinical ratings and biomechanical measures of upper extremity function. Methods: fMRI was used to compare the underlying changes in brain activity in PD patients following the administration of anti-parkinsonian medication and following a session of FE. Results: Nine individuals with PD completed fMRI scans under each condition: off anti-PD medication, on anti-PD medication, and off medication + FE. Unified Parkinson's Disease Rating Motor Scale scores improved by 50% in the FE condition compared to the off-medication condition. The pattern of fMRI activation after FE was similar to that seen with anti-PD medication. Direct comparison of the fMRI activation patterns showed high correlation between FE and anti-PD medication. Conclusion: These findings suggest that medication and FE likely utilize the same pathways to produce symptomatic relief in individuals with PD. Highlights: Acute forced-exercise, while off medication, resulted in a fMRI pattern of activation similar to anti-parkinsonian medication. The similarity between forced exercise and medication suggests a common mechanism of action within the brain contributing to symptomatic relief. The long-term effects of forced exercise is necessary understand the role of exercise on treatment of motor and non-motor symptoms.